2003
DOI: 10.1111/j.1572-0241.2003.07467.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fresh Frozen Plasma Infusion in Correction of Coagulopathy of Chronic Liver Disease: A Dual Phase Study

Wael I Youssef,
Fernando Salazar,
Srinivasan Dasarathy
et al.

Abstract: Our results reiterate previous observations made more than 45 yr ago, that fresh frozen plasma infusions using the number of units commonly employed in clinical practice infrequently correct the coagulopathy of patients with chronic liver disease. Higher volumes (6 or more units) may be more effective but are rarely employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(47 citation statements)
references
References 20 publications
(20 reference statements)
1
43
0
3
Order By: Relevance
“…During massive blood transfusion, FFP administration was advised at a ratio of 1:2 with red cells infusion, to avoid dilution of coagulation factors [144]. In patients with INR > 1.5, FFP was administered at a dosage of 12-15 mL/kg before liver biopsy, but evidence was not provided on whether or not this practice improved clinical outcomes [146]. In two studies this regimen allowed correction of PT in only 20% of patients receiving 900 mL of FFP [145,146].…”
Section: Fresh Frozen Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…During massive blood transfusion, FFP administration was advised at a ratio of 1:2 with red cells infusion, to avoid dilution of coagulation factors [144]. In patients with INR > 1.5, FFP was administered at a dosage of 12-15 mL/kg before liver biopsy, but evidence was not provided on whether or not this practice improved clinical outcomes [146]. In two studies this regimen allowed correction of PT in only 20% of patients receiving 900 mL of FFP [145,146].…”
Section: Fresh Frozen Plasmamentioning
confidence: 99%
“…In patients with INR > 1.5, FFP was administered at a dosage of 12-15 mL/kg before liver biopsy, but evidence was not provided on whether or not this practice improved clinical outcomes [146]. In two studies this regimen allowed correction of PT in only 20% of patients receiving 900 mL of FFP [145,146]. The infusion of <500 mL of FFP seldom corrects the PT by more than 2-3 s [142,147].…”
Section: Fresh Frozen Plasmamentioning
confidence: 99%
“…Variceal bleeding in cirrhosis carries a mortality of 7–15% [25]. The use of fresh frozen plasma (FFP) in patients with cirrhosis and portal hypertension has been shown to increase portal pressures in a linear fashion based upon volume [26]. A study by Youssef points out that increased doses of FFP are often required to improve coagulopathy in chronic liver disease patients who were unresponsive to vitamin K therapy, highlighting that six units were associated with greater correction than compared to those receiving less than six units – a significant amount of volume [27].…”
Section: Discussionmentioning
confidence: 99%
“…Youssef et al reported on FFP transfusions in 100 adult patients with liver disease, and found that it was difficult to correct abnormalities unless large volumes of FFP (6 units) were infused and the correction was short-lived. 52 The prophylactic administration of FFP has not been shown to decrease the risk of bleeding or to improve outcome. 53 Auzinger et al showed that percutaneous tracheostomy in patients with liver disease and resistant coagulopathy in whom the INR could not be lowered to Ͻ 1.6 or the platelets increased to Ͼ 50 000 cells/dL was not accompanied by a higher bleeding rate than in patients in whom the INR and/or platelet count could be corrected before the procedure.…”
Section: Ffpmentioning
confidence: 99%